The Commodification of Family Scandals on YouTube: Capitalist Logic in the Norma Risma Interview Phenomenon - Hadibroto, Joko Utomo; Nurdiansyah, Dian; Nathalia, Perdhani S (Advances in Social Sciences Research Journal, 2025)
The development of digital platforms has blurred the boundaries between private and public spheres, particularly when family scandals are packaged as interview content on YouTube to attract attention and economic gains. Taking the viral case of Norma Risma (2022–2025) which originated on TikTok, was subsequently reproduced in a series of YouTube interviews, and culminated in a feature film adaptation Norma: Antara Mertua dan Menantu (released in cinemas in March 2025 with approximately 662,000 viewers and on Netflix in August 2025, achieving 2.5 million views in two weeks and entering the global top 10 non-English titles) this study analyzes the commodification of private narratives within the logic of platform capitalism. A descriptive qualitative approach was employed, utilizing digital observation and online documentation of YouTube videos, news reports, and engagement data. The analysis integrates Vincent Mosco’s concept of commodification, Karl Marx’s and Pierre Bourdieu’s theories of capital, and the attention economy framework. The findings reveal three primary mechanisms: (1) dramatic packaging of narratives through sensational titles and emotional thumbnails, (2) accumulation of economic, social, cultural, and symbolic capital by creators and subjects, and (3) amplification of virality by YouTube’s algorithm. This phenomenon underscores the normalization of exploiting private experiences as digital commodities for advertising monetization.